Healthcare Resource Use and Burden Associated with Influenza Transmission Among Household Members with a Primary Infection: Commercial Claims Data Analysis - Wallick C; Abbass IM; Sheinson D; Moawad D (Dove Medical Press, 2021)
Christopher Wallick, Ibrahim M Abbass, Daniel Sheinson, Dalia Moawad Genentech, Inc, South San Francisco, CA, USACorrespondence: Christopher WallickGenentech, Inc., South San Francisco, CA, USATel +1 650-797-3006Fax +1 650-225-4630Email wallick.christopher@gene.comPurpose: To assess the burden of influenza transmission and care-seeking patterns over 3 influenza seasons among commercially insured households with a primary influenza infection.Patients and Methods: This retrospective cohort study used commercial claims data from the US MarketScan® Commercial and Medicare Supplemental databases for the 2014, 2015, and 2016 influenza seasons. Patients with a billed diagnosis of influenza and with coverage for at least 1 household member under the same health plan policy were included. A secondary diagnosed case was defined as a diagnosis of influenza in a second household member occurring within 14 days of the index case in a household.Results: Among 1,224,808 households with ≥ 2 members and a primary case of influenza, a secondary case of influenza was reported in 119,883 households (9.8%). A secondary diagnosed case of influenza occurred within 4 days of the primary diagnosis in 93,883 (78.3%) of those households. Both primary and secondary diagnosed influenza cases occurred most often among children (∼ 60%). Household size was positively correlated to both the risk of a second case (6.4% of households with 2 or 3 members versus 12.6% of households with ≥ 4 members, P < 0.001) and the time to diagnosis of a second case (Spearman rank correlation coefficient = 0.09; P < 0.001).Conclusion: Claims data for 3 influenza seasons (2014, 2015, 2016) showed that intrahousehold transmission of influenza occurs in approximately 10% of households with a primary case and poses a higher burden on larger households. Intrahousehold transmission of influenza represents a large healthcare resource use burden, with an unmet need for interventions that limit transmission.Keywords: claims, household, influenza, retrospective, observational, children